Analisis Kelengkapan Pengisian Resume Medis Rawat Inap di RS Darurat Covid-19 Wisma Atlet Kemayoran - Lutfi Rinaldi Syahbana; Indang Trihandini (Akademi Perekam dan Informasi Kesehatan Imelda, 2022)
The completeness of medical records is very important to affect the process of services provided by health workers and impact on the quality of services of a hospital. Preliminary study results conducted at RSDC Wisma Atlet Kemayoran, filling out medical resume form 5 out of 10 files no signature name of medical resume form. Also found, 3 out of 10 files have no outgoing diagnostic information. The purpose of this study is to identify the completeness of the patient's identity, review of important reports, authenticity review and review of the correct completeness of the medical resume form at RSDC Wisma Atlet Kemayoran. This research is qualitative research. The study subject consisted of 2 doctors who filled out a medical resume. The object of the study was a sample of inpatient medical records from June 7-21, 2021 based on slovin formula as many as 98 files. The results of the study on the completeness of filling a medical resume seen from 4 aspects have not been high enough. Incomplete filling of medical resume forms is influenced by several factors, namely man, methode, material, and machine factors.